(untitled) (Journal of Entrepreneurship and Business, 2022)
Malaysia ranked 14th in entrepreneurship in 2021. This shows that the Malaysian government has promoted entrepreneurship at the tertiary level. Not all graduates become entrepreneurs. Instead of starting a business, graduates take low-paying jobs unrelated to their skills. This study examined private university students’ intentions to become entrepreneurs and their motivation, creativity, attitude, ability, and university ecosystem. Additionally, this study examined the mediating effect of motivation on creativity, attitude, ability, university ecosystem, and entrepreneur intention among private university students. SPSS was used to analyse the 215 samples of private university students in the northern region of Malaysia. Findings postulate that only motivation and attitude affect a student’s intention to become an entrepreneur. Motivation mediates between students’ attitudes and entrepreneurial intentions. This study helps institutions, teachers, and policymakers understand what makes private university students want to start their own businesses. This means that strategies and policies can be changed in the future to encourage private university students to go into the entrepreneurship field. Keywords: Entrepreneurial intention,